2022
DOI: 10.1136/rmdopen-2022-002250
|View full text |Cite
|
Sign up to set email alerts
|

Role of vertebral corner inflammation and fat deposition on MRI on syndesmophyte development detected on whole spine low-dose CT scan in radiographic axial spondyloarthritis

Abstract: ObjectivesTo investigate the associations between MRI detected vertebral corner inflammation (VCI) and vertebral corner fat deposition (VCFD) on whole spine low-dose CT scan (ldCT) detected syndesmophyte formation and growth.MethodsPatients from the Sensitive Imaging in Ankylosing Spondylitis cohort underwent MRI (baseline, 1 year and 2 years) and ldCT (baseline and 2 years). MR images were scored by three readers for VCI and VCFD, MRI patterns were defined by presence of VCI and/or VCFD over 2 years. LdCT ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
3
13
0
1
Order By: Relevance
“…Similar results have already been shown at the vertebral unit level in studies using radiographs, 24 32 but also using ldCT scans in the SIAS cohort. 31 Since no effect of inflammation-driven bone loss on subsequent bone formation was shown in our study, taken together, these results suggest a solid independent direct effect of inflammation on bone formation. In this scenario, trabecular bone loss and peripheral bone formation may coexist as a consequence of inflammation at the same vertebra.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Similar results have already been shown at the vertebral unit level in studies using radiographs, 24 32 but also using ldCT scans in the SIAS cohort. 31 Since no effect of inflammation-driven bone loss on subsequent bone formation was shown in our study, taken together, these results suggest a solid independent direct effect of inflammation on bone formation. In this scenario, trabecular bone loss and peripheral bone formation may coexist as a consequence of inflammation at the same vertebra.…”
Section: Discussionsupporting
confidence: 55%
“…However, these results should be interpreted with extreme caution due to relevant pitfalls: only few vertebrae were included, trabecular bone density variation throughout the spine was not accounted for, 28 30 and the analyses were not adjusted for local vertebral inflammation, a known relevant confounder for this relationship. 31 Though out of the scope of our research questions, when included as a confounder, the presence of MRI-BME at baseline was associated with a nearly twofold higher probability of 2-year syndesmophyte formation or growth, with this association persisting in multivariable analysis. Similar results have already been shown at the vertebral unit level in studies using radiographs, 24 32 but also using ldCT scans in the SIAS cohort.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A recent study showed that vertebral corner inflammation and vertebral corner fat deposition were positively associated with syndesmophyte development. However, almost half of bone formation occurred in corners without vertebral corner inflammation/fat deposition, suggesting the presence of these MRI lesions does not fully clarify the development of syndesmophytes, and low dose CT can be a useful tool for monitoring bone formation of whole spine in research ( 38 ). Third, the retrospective design of this study is a shortcoming.…”
Section: Discussionmentioning
confidence: 99%
“…47 The important issue of replacing CR by low-dose CT in detail is beyond the scope of this editorial-even though there is increasing evidence that it does capture the whole spine (in contrast to CR and scoring with the mSASSS) and it is more sensitive to change. 21 What about the consequences of structural changes related to function and mobility? There is evidence that both, inflammation and structural changes in the spine, have an impact on function and mobility.…”
Section: Spondyloarthritis Spondyloarthritis Spondyloarthritismentioning
confidence: 99%